The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/art.41309
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Induces Obliterative Pulmonary Vascular Disease in a Novel Model of Connective Tissue Disease–Associated Pulmonary Arterial Hypertension

Abstract: Objective. Connective tissue disease (CTD)-associated pulmonary arterial hypertension (PAH) is the second most common etiology of PAH and carries a poor prognosis. Recently, it has been shown that female human tumor necrosis factor (TNF)-transgenic (Tg) mice die of cardiopulmonary disease by 6 months of age. This study was undertaken to characterize this pathophysiology and assess its potential as a novel model of CTD-PAH. Methods. Histologic analysis was performed on TNF-Tg and wild-type (WT) mice to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…RA complicated with heart disease, including myocardial hypertrophy, myocardial fibrosis, and RA-ILD including pulmonary fibrosis and inflammatory infiltration, have been reported in other animal models of RA ( Bell et al, 2020 ; Keith et al, 2012 ; Pironti et al, 2018 ; Redente et al, 2018 ). For the TNF-Tg model used in this study, It has been previously reported that TNF-Tg mice have lung lesions, including pulmonary inflammatory cell accumulation, pulmonary arteriole thickening, pulmonary fibrosis, and emphysema ( Lundblad et al, 2005 ; Bell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 90%
“…RA complicated with heart disease, including myocardial hypertrophy, myocardial fibrosis, and RA-ILD including pulmonary fibrosis and inflammatory infiltration, have been reported in other animal models of RA ( Bell et al, 2020 ; Keith et al, 2012 ; Pironti et al, 2018 ; Redente et al, 2018 ). For the TNF-Tg model used in this study, It has been previously reported that TNF-Tg mice have lung lesions, including pulmonary inflammatory cell accumulation, pulmonary arteriole thickening, pulmonary fibrosis, and emphysema ( Lundblad et al, 2005 ; Bell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 90%
“…[ 32 ] A TNF‐transgenic model was recently shown to develop spontaneous and severe pulmonary hypertension and have genomic overlap with SSc‐PAH but to lack systemic fibrosis. [ 33 ] Another model is represented by urokinase‐type plasminogen activator receptor (uPAR)‐deficient mice. Urokinase‐type plasminogen activator receptor is a glycosylphosphatidylinositol‐anchored cell surface receptor which concentrates its ligand, urokinase‐type plasminogen activator (uPA), at the cell–matrix interface.…”
Section: Animal Models Of Sscmentioning
confidence: 99%
“…Likewise, the ODE group lacked clusters 1a and 2a. A subset of cluster 12 (12b) and cluster 10 (10b) were [22] unique to the CIA group, while clusters 10a and 12a were unique to the ODE group (Fig 3). The combination group with CIA+ODE showed a mixed population representing CIA and ODE, while leaning more towards the CIA group (Fig 3).…”
Section: Cia and Ode Drive Unique Distributions Of Immune Cells Within Identified Clustersmentioning
confidence: 99%
“…In general, animal modeling of arthritis-lung disease interactions are overall limited. The over-expressing TNF-alpha transgenic mice that develop an array of connective tissue diseases has been associated with interstitial lung disease and pulmonary hypertension, particularly in female mice [22]. The arthritic SKG mice develop a cellular and fibrotic interstitial pneumonia [140], but SKG mice do not develop compelling evidence of autoimmunity or arthritis following inhalation injury (i.e tobacco smoke or bleomycin) [140].…”
Section: Plos Onementioning
confidence: 99%